2012
DOI: 10.1038/bjc.2011.574
|View full text |Cite
|
Sign up to set email alerts
|

Effect of κ-opioid receptor agonist on the growth of non-small cell lung cancer (NSCLC) cells

Abstract: Background:It is becoming increasingly recognised that opioids are responsible for tumour growth. However, the effects of opioids on tumour growth have been controversial.Methods:The effects of κ-opioid receptor (KOR) agonist on the growth of non-small cell lung cancer (NSCLC) cells were assessed by a cell proliferation assay. Western blotting was performed to ascertain the mechanism by which treatment with KOR agonist suppresses tumour growth.Results:Addition of the selective KOR agonist U50,488H to gefitinib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 15 publications
1
33
0
Order By: Relevance
“…As with GIPR, its endogenous ligands, the dynorphins, are well described and agonist and antagonist molecules are available 24 . In addition to previous reports of OPRK1 expression in a breast adenocarcinoma cell line and small-cell lung cancer, it was recently reported that OPRK1 is overexpressed by gefitinib-sensitive and resistant non-small cell lung cancer cell lines as compared to normal lung fibroblasts 25 . In these cells, treatment with the agonist U50,488H caused markedly decreased growth and blocked phosphorylation of GSK-3β, particularly in gefitinib-resistant cells.…”
Section: Discussionmentioning
confidence: 79%
“…As with GIPR, its endogenous ligands, the dynorphins, are well described and agonist and antagonist molecules are available 24 . In addition to previous reports of OPRK1 expression in a breast adenocarcinoma cell line and small-cell lung cancer, it was recently reported that OPRK1 is overexpressed by gefitinib-sensitive and resistant non-small cell lung cancer cell lines as compared to normal lung fibroblasts 25 . In these cells, treatment with the agonist U50,488H caused markedly decreased growth and blocked phosphorylation of GSK-3β, particularly in gefitinib-resistant cells.…”
Section: Discussionmentioning
confidence: 79%
“…32 Our findings are in accord with reports that the Ga icoupled GABA-B receptors have tumor suppressor function in NSCLC 15,25,33 and that Ga i -coupled KORs and DORs inhibit the proliferation of NSCLC cells in vitro. 18,19 The cited findings were generated with NSCLC cell lines that contained only small populations of cancer stem cells and therefore largely reflected the responses of differentiated cancer cells. Our current findings in CSC spheroids indicate that Ga i -signaling in response to GABA and opioid peptides also exerts significant inhibitory actions on CSCs.…”
Section: Discussionmentioning
confidence: 99%
“…These responses were inhibited by gene knockdown of the β1‐adrenergic receptor or by treatment with the inhibitory neurotransmitter γ‐aminobutyric acid (GABA), which activated the inhibitory G‐protein Gα i coupled to GABA‐B receptors, thus inhibiting the formation of cAMP . Moreover, it has been shown that low concentrations of agonists for delta and kappa‐opioid receptors (DORs, KORs) that are also coupled to Gα i inhibited the growth of NSCLC cell lines …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, relatively little is known about direct involvement of the k opioid receptor in cancer. More information would be welcome, since a study this year showed that a selective k agonist inhibits the growth of non-SCLC cells, in naloxone-reversible fashion, through a mechanism involving death-promoting glycogen synthase kinase 3b [85]. Scant information is available relating the fourth recognized opioid receptor, ORL 1 , to cancer.…”
Section: Perspectivesmentioning
confidence: 99%